A Multi‐Gradient Targeting Drug Delivery System Based on RGD‐l‐TRAIL‐Labeled Magnetic Microbubbles for Cancer Theranostics. (4th October 2016) - Duan, Lei; Yang, Fang; He, Wen; Song, Lina; Qiu, Fan; Xu, Ning; Xu, Lu; Zhang, Yu; Hua, Zichun; Gu, Ning
Abstract : The accurately and efficiently targeted delivery of therapeutic/diagnostic agents into tumor areas in a controllable fashion remains a big challenge. Here, a novel cancer targeting magnetic microbubble is elaborately fabricated. First, the γ‐Fe2 O3 magnetic iron oxide nanoparticles are optimized to chemically conjugate on the surface of polymer microbubbles. Then, arginine‐glycine‐aspartic acid‐l ‐tumor necrosis factor‐related apoptosis‐inducing ligand (RGD‐l ‐TRAIL), antitumor targeting fusion protein, is precisely conjugated with magnetic nanoparticles of microbubbles to construct RGD molecularly targeted magnetic microbubble, which is defined as RGD‐l ‐TRAIL@MMBs. Such RGD‐l ‐TRAIL@MMBs is endowed with the multigradient cascade targeting ability following by magnetic targeting, RGD, as well as enhanced permeability and retention effect regulated targeting to result in high cancerous tissue targeting efficiency. Due to the highly specific accumulation of RGD‐l ‐TRAIL@MMBs in the tumor, the accurate diagnostic information of tumor can be obtained by dual ultrasound and magnetic resonance imaging. After imaging, the TRAIL molecules as anticancer agent also get right into the cancer cells by nanoparticle‐ and RGD‐mediated endocytosis to effectively induce the tumor cell apoptosis. Therefore, RGD‐l ‐TRAIL conjugated magnetic microbubbles could be developed as a molecularly targeted multimodality imaging delivery system with the addition of chemotherapeutic cargoes to improve cancer diagnosis and therapy. Abstract : The optimized arginine‐glycine‐aspartic acid‐l‐tumor necrosis factor‐related apoptosis‐inducing ligand (RGD‐l‐TRAIL) protein modified novel magnetic microbubble delivery system is endowed with a multigradient cascade targeting strategy followed by magnetic field, RGD, as well as enhanced permeability and retention effect targeting. The results demonstrate highly targeted dual ultrasound and magnetic resonance imaging and targeted TRAIL molecules for tumor selective apoptotic activity.